Does Financial Literacy Has Greater Role in Achieving Stock Investment Performance of College Investors? - Wijayanti, Risna; Juwita, Himmiyatul Amanah Jiwa (AIBPM Publisher, 2024)
This research aims to integrate the perspectives of rationality and irrationality, which cannot be separated in capital market participants, especially young investors, in the decision-making process of stock investment. The research emphasizes whether cognitive factors, which including financial literacy and play a more significant role. Additionally, overconfidence as behavioral aspect can serve as a mediator linking financial literacy and investment performance. Conducted on 77 students who invest in investment gallery in Malang, using random sampling techniques, the research is an explanatory study with a quantitative approach through a questionnaire processed by SEM-PLS analysis using Smart PLS 3.0. Based on the findings of this study highlight the positive influence of financial literacy on stock investment performance, while overconfidence was found to have mediating effect on relationship between financial literacy and stock investment performance. The characteristics of respondents who are young age with limited funds for stock investment leads to low expectations of returns, resulting in quick satisfaction and then affecting stock investment performance